+0

# cubed root (9+4 sqrt 5)+cubed root (9-4 sqrt 5) = 3

0
4
366
8

how to prove it

thanks.

Guest Nov 6, 2014

#5
+17711
+10

CPhill's answer is, in the words of one of my instructors, elegant.

That won't be said for mine; more like a brute force attempt:

To make the typing easier,

let  A  =  (9 + 4√5)^(1/3)          --->          A³  =  9 + 4√5

let  B  =  (9 - 4√5)^(1/3)           --->          B³  =  9 - 4√5

Let  X  =  A + B             So, now:  X  = (9 + 4√5)^(1/3) + (9 - 4√5)^(1/3)    (the problem)

Also:   A·B  =  [ (9 + 4√5)^(1/3) ] · [ (9 - 4√5)^(1/3) ]

=  [ (9 + 4√5) · (9 - 4√5) ] ^(1/3)

=  [ 81 - 16 · 5 ] ^(1/3)

=  [ 1 ] ^(1/3)

=  1

Since  A·B  =  1,

A²·B  =  A(AB)  =  A(1)  =  A  =  (9 + 4√5)^(1/3)

A·B²  =  (AB)B  =  (1)B  =  B  =  (9 - 4√5)^(1/3)

Sinc  X  =  A + B,

X³  =  (A + B)³  =  A³ + 3A²·B + 3A·B² + B³

X³  =  (9 + 4√5) + [ 3(9 + 4√5)^(1/3) ] + [ 3(9 - 4√5)^(1/3) ] + ( 9 - 4√5 )

Rearranging:

X³  =  18 + 3[ (9 + 4√5)^(1/3) + (9 - 4√5)^(1/3) ]

X³  =  18 + 3[ A + B ]

But, since A + B  =  X

X³  =  18 + X

X³ - X - 18  =  0

Factoring:

(X - 3)(X² + 3X + 6)  = 0

So:  X = 3  or X = [-3 ± i√(15) ] / 2

Since the answer is a pure real number, the answer is  3!

geno3141  Nov 6, 2014
Sort:

#1
+91435
0
##### $$\sqrt[3]{(9+4 \sqrt 5}+\sqrt[3]{(9-4 \sqrt 5} = 3$$

Umm I do not know - I'll have to think about this one!

Melody  Nov 6, 2014
#2
+80935
+10

This one is tricky.....but note.....(9 + 4√5)^(1/3) = (Phi)2  where Phi = (1 + √5)/2

And (9 -4√5)^(1/3) = phi2 = Phi -2 where Phi -1  = phi = 2/(1 + √5)

So we have

Phi 2 + Phi -2   =

Phi 2 + phi 2       and by a property of Phi and phi......Phi2 = 1 + Phi   and phi2 = 1 - phi ... so we have

(1 + Phi)  + (1 - phi) =

2 + Phi - phi            and by another property of Phi and phi.....Phi - phi = 1    so we have

2 + 1 = 3

CPhill  Nov 6, 2014
#3
+91435
0

....but note.....(9 + √80)^(1/3) = (Phi)2  where Phi = (1 + √5)/2

Christ Chris, What archive did you dig that out of !

Melody  Nov 6, 2014
#4
+80935
+5

When I evaluated (9  + √80)^(1/3) and (9 - √80)^(1/3), I immediately saw that these were related to Phi and phi.....

CPhill  Nov 6, 2014
#5
+17711
+10

CPhill's answer is, in the words of one of my instructors, elegant.

That won't be said for mine; more like a brute force attempt:

To make the typing easier,

let  A  =  (9 + 4√5)^(1/3)          --->          A³  =  9 + 4√5

let  B  =  (9 - 4√5)^(1/3)           --->          B³  =  9 - 4√5

Let  X  =  A + B             So, now:  X  = (9 + 4√5)^(1/3) + (9 - 4√5)^(1/3)    (the problem)

Also:   A·B  =  [ (9 + 4√5)^(1/3) ] · [ (9 - 4√5)^(1/3) ]

=  [ (9 + 4√5) · (9 - 4√5) ] ^(1/3)

=  [ 81 - 16 · 5 ] ^(1/3)

=  [ 1 ] ^(1/3)

=  1

Since  A·B  =  1,

A²·B  =  A(AB)  =  A(1)  =  A  =  (9 + 4√5)^(1/3)

A·B²  =  (AB)B  =  (1)B  =  B  =  (9 - 4√5)^(1/3)

Sinc  X  =  A + B,

X³  =  (A + B)³  =  A³ + 3A²·B + 3A·B² + B³

X³  =  (9 + 4√5) + [ 3(9 + 4√5)^(1/3) ] + [ 3(9 - 4√5)^(1/3) ] + ( 9 - 4√5 )

Rearranging:

X³  =  18 + 3[ (9 + 4√5)^(1/3) + (9 - 4√5)^(1/3) ]

X³  =  18 + 3[ A + B ]

But, since A + B  =  X

X³  =  18 + X

X³ - X - 18  =  0

Factoring:

(X - 3)(X² + 3X + 6)  = 0

So:  X = 3  or X = [-3 ± i√(15) ] / 2

Since the answer is a pure real number, the answer is  3!

geno3141  Nov 6, 2014
#6
+91435
0

Thanks Chris and Gino :)))

Melody  Nov 7, 2014
#7
+80935
0

Very nice, Geno.....I would dispute that mine is more "elegant"....more like...."calculator aware".... LOL!!!

(Plus.....a little knowledge about the proprties of Phi and phi....!!)

CPhill  Nov 7, 2014
#8
+91435
0

Yea well - it is all still too much for me LOL  :)))

Melody  Nov 8, 2014

### 14 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details